Anti-inflammatory effect of schizandriside isolated from Memecylon scutellatum Lour in lipopolysaccharide-stimulated raw 264.7 murine macrophages - Duong, Thu Trang; Tran, Tuan Anh; Nguyen, Quang Huy; Nguyen, Thi Trang Huyen; Do, Thi Trang; Duong, Thi Dung; Nguyen, Trang Linh; Tran, Huong Giang; Tuan Phuong, Nguyen; Phuong Minh, Nguyen; et al. (Academia Journal of Biology, 2025)
Inflammation plays a key role in increasing the risk of chronic diseases such as diabetes, rheumatoid arthritis, and cancer. The Memecylon genus is known for its antioxidant, antidiabetic, anticancer, and antimicrobial properties. However, the anti-inflammatory activity of the Memecylon scutellatum Lour remains poorly understood. Therefore, this study aimed to explore the anti-inflammatory effects of schizandriside, a compound isolated from the leaves of M. scutellatum in lipopolysaccharide (LPS)-stimulated RAW 264.7 murine macrophages. Nitric oxide (NO) production was measured using the Griess assay, TNF-α and IL-6 secretion were quantified through Elisa and iNOS, COX-2 protein level was analyzed by Western blotting. The results demonstrated that schizandriside reduced the production of NO, TNF-α and IL-6 production and strongly inhibited iNOS, COX-2 protein expression in LPS-stimulated RAW 264.7 cells. This data suggested that schizandriside has strong potential as an anti-inflammatory agent for treating inflammatory diseases.